Hepatocellular carcinoma and possibility of liver transplantation: evaluation and emotional aspects - Warwar, Maria Isabel (2013)
Liver transplantation is a therapeutic alternative for patients with end-stage liver diseases including hepatocellular carcinoma. After being inserted on the waiting list, there is relief, and shortly, the perception of the waiting, where patients have no control. Thus, the waiting period is the most stressful, as the disease is fully active. Often, clinical deterioration becomes more apparent, resulting in prolonged hospitalization. During this step, it may appear clinical contraindication which may make the transplant impossible, such as infections, brain damage and hemodynamic instabilities. At this occasion, the psychologist and religious assistance can help both patients and families in such transition and to prepare them for a mourning period. Experience shows that a certain level of psychological adjustment is required for a successful pre- and post-transplant in patients with HCC. Contribution of a psychologist is to introduce and respect the patient’s subjective dimension throughout the transplant process. For this reason, the earlier the transplant team detects cognition or behavior psychosocial issues, it may have opportunity to develop treatment plans to minimize any negative impact these problems can cause to a successful transplantation.